PENGARUH PENGUNGKAPAN CSR, KEPEMILIKAN INSTITUSIONAL, DIVERSIFIKASI, STRUKTUR MODAL, DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN (Study Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2013-2015) - Wahyu Tri Setyoasri, 13.05.52.0200; Poerwati, Tjahjaning (Students' Journal of Accounting and Banking, 2017)
This study aims to analyze the influence of CSR disclosure, institutional ownership, diversification, capital structure, and firm size on the company's financial performance. In this study the sample used is manufakturing companies listed on the Indonesia Stock Exchange (BEI) in 2013-2015. Sampling technique in this research use purposive sampling. The technique of data testing using multiple linear regression analysis. The result of analysis shows that CSR variable has an effect on to company financial performance. Institutional ownership affects the company's financial performance. Diversification does not affect the company's financial performance. Capital Structure affect the financial performance of the company. The size of the company affects the financial performance of the company.Keywords: CSR, Institutional Ownership, Diversification, Capital Structure, and Firm Size, Corporate Financial Performance